Enhancing the achievement in physics’ motion concept through online multiple intelligence learning approach - Ahamad, Adri Nirwan; Samsudin, Mohd Ali; Ismail, Mohd Erfy; Ahmad, Nur Jahan (2021)
The complexity of physics concepts in online learning environment probably will only benefit certain group of students. Thus, there are suggestions that the approach of delivering physics concepts in online learning environment shoud be conducted in various ways. The purposed of research was to investigate the effect of online multiple intelligence-based learning on achievement in physics’ motion concept among 10th grade students. The one group pre-test and post-test design were used in this research with purposive sampling, with 30 students in a science junior high school in Malaysia. In the research, the data were obtained from Multiple Intelligence Test and Physics Force and Motion Concept Test, which were analyzed using one-way ANOVA and non-parametric test Wilcoxon and Friedman. The findings reveal that online multiple intelligence-based learning had an effect on the achievement in physics’ force and motion concepts with mathematical logic and Intrapersonal intelligence group performed significantly better than others.